Evaluasi Pembelajaran Ditinjau Dari Al-qur'an Surah Al-ankabut Ayat 2-3 - Hasanah, Nurul; Badriyah, Lailatul; Diamard Selia, Wena (JPT : Jurnal Pendidikan Tematik, 2020)
Evaluation is one component in an education system that involves teachers and students. This means that the evaluation must be done systematically and planned. Evaluation is used as a tool to assess and measure a success in the education process. Al-Qur'an as the main source of Islamic education, and also many express the concept of evaluation in the verses as a reference for humans to be careful in doing their deeds. In the Qur'an the term evaluation does not have a definite word meaning but there are words that can be used as a reference to interpret the words of evaluation, such as Al-Bala, Al-Hukm, Al-Qodha, Al-Nazr and Al-Fitnah . This research uses literature study by studying several books and journals. The results of this study are expected for students and teachers to better understand the meaning of the word evaluation in education and in Islamic education.